Academic Senate Minutes 2003-10-02 - Academic Senate:::::::::
Announcements from Chair-Elect. Agenda modified and approved. Minutes approved. Consent item Appointments to the Disabled Student Services Advisory Committee as interim reps: Elaine McHugh and Barbara Lesch McCaffry approved. Report from Provost. From S&F: Procedures for emergency Senate action tabled. Discussion Item: Joint CSU/CFA 2003-04 Supplemental Report Language document & Resolution from the Lecturer's Council regarding Enterprises surplus first reading. Long Range Academic Plan first reading. Report from Associated Student President. Report from APC.